2020
DOI: 10.1038/s41408-020-00385-0
|View full text |Cite
|
Sign up to set email alerts
|

Race/ethnicity in systemic AL amyloidosis: perspectives on disease and outcome disparities

Abstract: In marked contrast to multiple myeloma, racial/ethnic minorities are underrepresented in publications of systemic light-chain (AL) amyloidosis. The impact of race/ethnicity is therefore lacking in the narrative of this disease. To address this gap, we compared disease characteristics, treatments, and outcomes across racial/ethnic groups in a referred cohort of patients with AL amyloidosis from 1990 to 2020. Among 2416 patients, 14% were minorities. Non-Hispanic Blacks (NHBs) comprised 8% and had higher-risk so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
0
17
0
2
Order By: Relevance
“…Systematic underdetection is also thought to be a large part of the problem because the structural heart changes, proteinuria, and neuropathy seen with AL amyloidosis can be misattributed to hypertension or diabetes mellitus, both of which are more prevalent in racial minorities. 7 …”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic underdetection is also thought to be a large part of the problem because the structural heart changes, proteinuria, and neuropathy seen with AL amyloidosis can be misattributed to hypertension or diabetes mellitus, both of which are more prevalent in racial minorities. 7 …”
Section: Epidemiologymentioning
confidence: 99%
“…For instance, while we know that germline expression of the IGLV1-44 gene is associated with cardiac tropism and the IGLV6-57 gene is associated with renal tropism, variances in gene expression with regard to race or ethnicity haven’t been assessed. 7 …”
Section: Epidemiologymentioning
confidence: 99%
“…Согласно имеющимся статистическим данным, заболеваемость этой формой амилоидоза в западных странах составляет 1 случай на 100000 человеко-лет, при этом системный амилоидоз встречается чаще, чем локальный [7]. Доказано, что расовые и этнические особенности не влияют на распространенность, тяжесть заболевания и эффективность лечения ALамилоидоза [8].…”
Section: амилоидоз легких цепейunclassified
“…The likelihood of obtaining only a partial-HLA match in Hispanics was [OR 1.73 (1.41-2.12)] when compared to white patients in a study by Dehn et al (4), whereas Besse et al (5) showed that Hispanic patients in the 20-25 years old age group had similar odds of finding an HLA-match (40%) when compared to white patients (25-30%). Utilization of HSCT by Hispanic patients was evaluated by three retrospective reviews (6)(7)(8). Costa et al (6) developed a relative utilization rate (RUR) which compared a particular group's utilization of autologous HSCT in multiple myeloma patients as a proportion of the utilization of the entire population.…”
Section: Hispanic Disparities In Access To Hsctmentioning
confidence: 99%